RTRIPLEXCWFlux: An R package for carbon–water coupling model to simulate net ecosystem productivity and evapotranspiration in forests. (April 2023) - Sun, Shulan; Ouyang, Shuai; Hu, Yanting; Zhao, Zhonghui; Liu, Meixian; Chen, Liang; Zeng, Yelin; Peng, Changhui; Zhou, Xiaolu; Xiang, Wenhua
Abstract: Carbon and water cycles in forest ecosystems are tightly coupled, but global warming-induced soil and atmospheric droughts alter the coupling, thereby greatly increasing uncertainty in predicting carbon and water cycles. Therefore, a carbon–water coupled model (TRIPLEX-CW-Flux) was developed, and an R package (rTRIPLEXCWFlux) was created to facilitate model application. TRIPLEX-CW-Flux integrates vapor pressure deficit and soil moisture into a stomatal conductance submodule to estimate forest carbon and water fluxes. Prediction accuracy of TRIPLEX-CW-Flux and rTRIPLEXCWFlux application were evaluated in a Chinese fir ( Cunninghamia lanceolata ) plantation. Simulated net ecosystem production ( NEP ) and evapotranspiration ( ET ) were in good agreement with flux observations ( R 2 : 0.76 for NEP ; 0.71 for ET ). Thus, the TRIPLEX-CW-Flux model can be used to predict and quantify effects of global warming-induced droughts on forest carbon and water cycles. The open-access rTRIPLEXCWFlux package facilitates estimations of carbon sequestration and water consumption in forest ecosystems using the observed flux data. Highlights: A physiological process model that couples carbon and water flux was developed. Both atmospheric and soil drought stress were also integrated into the model. An R package was encoded for the model to predict forest carbon and water flux. The simulated values were comparable to the flux data observed in the forest. This R package can be used to evaluate forest functions under climate change.